Identifying an effective last-mile customer delivery option with an integrated eco-friendly inventory model. Issue 2 (16th May 2022) - Wangsa, Ivan Darma; Wee, Hui Ming; Hsiao, Yu Lin; Rizky, Novrianty
Abstract: In this study, we have developed an integrated inventory model for the last-mile delivery where the distributer supplies goods to his customers. Two services based on the type of deliveries are investigated, namely: 1) motorcycle delivery service, and 2) drone delivery service. The objective of this study is to identify an effective last-mile delivery option, considering both cost and eco-friendly factors. An algorithm is formulated to determine the optimal order quantity, safety factor, lead-time, total emission and the number of deliveries. The implication derived from our investigation is that: using motorcycle for the last-mile delivery may be faster than using drone, it is not as environmentally friendly. One of the disadvantages of using drone is the fact that current drone cannot carry too heavy loads or travel very long distances; we hope in the future more advanced drone will be able to overcome the disadvantage. Numerical examples and sensitivity analyses are provided to illustrate the proposed model. Finally, closing remarks and future research are given in the conclusion. From the comparison analysis, besides eco-friendly, the integrated total cost using drone is lower than motorcycle, with a cost-saving around 3-4%.